Identification and Distribution of Damage Intensity Caused by Sanurus spp. on Cashew Plants in East Flores Regency, Indonesia - Kleden, Yasinta L.; Kadja, Don H.; Nahas, Agustina E.; Widinugraheni, Sri; Pramatana, Fadlan (Universitas Panji Sakti, 2025)
Cashew is one of Indonesia's leading commodities as an exporting country because it has a positive trade specialization index. The main pest of cashew plants that affects production and can cause crop failure is the Cashew Planthopper (WPM). Cashew Planthopper has several species. Therefore, monitoring is needed to determine the types of WPM in the field and their distribution areas on the mainland of East Flores Regency. This study was conducted from May 2024 to July 2024 by directly capturing WPM imago. The results of a survey of cashew plantation locations in East Flores Regency, 5 locations were determined with high levels of attack due to WPM, which caused crop failure, namely: Ile Mandiri District, Lewolema District, Tanjung Bunga District, Titehena District, and Demon Pagong District. The trapped WPM were then identified by looking at the characteristics of the wings, thorax, and abdomen. The identification results obtained 2 types of WPM from the genus Sanurus, namely, Sanurus flavovenosus and Sanurus indecora. The distribution area of the attack and the level of damage to Sanurus from each district have different intensities with different levels of damage, namely the intensity of heavy damage in red is in Titehena District 53.04%, the intensity of moderate damage in yellow is in Lewolema District 20.65%, Ile Mandiri District 36.91% and Demon Pagong District 36.94% while the intensity of light damage in green is in Tanjung Bunga District 0.55%.